Effects of Scheduled Exercise on Cancer-Related Fatigue in Women with Early Breast Cancer - Anne Marie Lunde Husebø; Sindre Mikal Dyrstad; Ingvil Mjaaland; Jon Arne Søreide; Edvin Bru (The Scientific World Journal)
While physical activity during cancer treatment is found beneficial for breast cancer patients, evidence indicates ambiguous findings concerning effects of scheduled exercise programs on treatment-related symptoms. This study investigated effects of a scheduled home-based exercise intervention in breast cancer patients during adjuvant chemotherapy, on cancer-related fatigue, physical fitness, and activity level. Sixty-seven women were randomized to an exercise intervention group (n=33, performed strength training 3x/week and 30 minutes brisk walking/day) and a control group (n=34, performed their regular physical activity level). Data collection was performed at baseline, at completion of chemotherapy (Post1), and 6-month postchemotherapy (Post2). Exercise levels were slightly higher in the scheduled exercise group than in the control group. In both groups, cancer-related fatigue increased at Post1 but returned to baseline at Post2. Physical fitness and activity levels decreased at Post1 but were significantly improved at Post2. Significant differences between intervention and control groups were not found. The findings suggest that generally recommended physical activity levels are enough to relief cancer-related fatigue and restore physical capacity in breast cancer patients during adjuvant chemotherapy, although one cannot rule out that results reflect diminishing treatment side effects over time.